A patient from Zhejiang, China, with synchronous mucinous metaplasia and neoplasms of the female genital tract: A case report. Issue 7 (16th April 2019) - Lu, Jingjing; Gao, Li; Yu, Huimin; Xia, Liang; Guo, Xiuyu; Zheng, Fei
Abstract: Synchronous mucinous metaplasia and neoplasms of the female genital tract (SMMN‐FGT) is a rare disease reported by a few scholars without the consensus of diagnosis and treatment. Here we will report a 57‐year‐old female patient from Zhejiang China who suffered from this disease. She came to our hospital because of a large amount of vaginal discharge. All the medical examination was negative except hydrometra, and the left fallopian tube was segmenting and thickening. Then she had a total hysterectomy and a bilateral salpingo‐oophorectomy and was finally diagnosed with pathological evidence. In addition, the positron emission tomography‐computed tomography scan after the operation revealed no residual tumors, and the case needed further follow‐up.